Klinik-Weiterempfehlung bei Reha-Erfolg: Erfahrungsberichte von Rehabilitanden auf einer Klinik-Bewertungsplattform - Sander, Uwe; Biedermann, Irina; Emmert, Martin; Haaf, Hans Günter; Hofmann, Anna Lena; Hopf, Felix; Kiss, Susann; Parthier, Katrin; Schindler, Anja; Patzelt, Christiane (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2021)
Introduction: Feedback from patients about aspects of rehabilitation services is increasingly provided online, for example, on specialized hospital comparison websites. Therefore, we examined which kind of online statements from rehabilitation patients published on the leading hospital comparison website “Klinikbewertungen.de” (KB) is associated with a positive recommendation of a rehabilitation clinic and which negative aspects are associated with a non-recommendation. Methods: For eight indication groups stratified online statements of rehabilitants at KB were evaluated qualitatively using content analysis. The relationship between positive (negative) statements and the (non-) recommendation was examined. Results: Content analysis of 911 experience reports revealed 20 categories. Most often, it was the “rehabilitation success” perceived by rehabilitation patients that was significantly associated with a recommendation or a non-recommendation of a hospital, and in five quality assurance (QA) comparison groups the category “catering” was associated with a positive or negative recommendation. In all QS comparison groups, there was an association with at least one of the following process-oriented rehabilitation categories: “rehabilitation measures”, “rehabilitation plan and rehabilitation goals” and / or “diagnosis to discharge”. Discussion and Conclusion: Patient experiences with the perceived “rehabilitation success” and with the central processes of rehabilitation are particularly important for the recommendation or non-recommendation of a hospital for patients in all eight indication groups. On the basis of these results, rehabilitation hospitals can specifically identify the aspects of care that are important when patients recommend a hospital for rehabilitation. Online narratives of patients provide additional insights into the reasons for patients’ satisfaction or dissatisfaction with their rehabilitation. These narratives are available to potential rehabilitation patients as a low-threshold source of information and decision-making aid.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Experience reports; Patient satisfaction; Rehabilitation; Review sites; Social Media